Advanced circulatory support: artificial heart use in patients with heart failure / Suporte circulatório avançado: uso do coração artificial em pacientes com Insuficiência cardíaca - Paula, Luiza Miranda Marinho de (2020)
Objectives: To analyze recent clinical trials about mechanical circulatory support and other adjuvant therapies for the treatment of heart failure. Methods: Articles were selected from the Pubmed and Embase databases published between the years 2015 and 2020, randomized controlled trial or not. The descriptors used were: assisted circulation AND artificial heart AND heart failure, and the descriptor artificial heart was not used for research at EMBASE with 2 articles as results.  And 40 at PubMed with the filters: Controlled Clinical Trial, published in the last 5 years, Humans. Results: Several therapies have been proposed as management alternatives for critically ill patients with heart failure. Among them, we can highlight the HeartMate III implant, which has been shown to have fewer adverse effects compared to HeartMate II; the implantation of an atrial bypass device, which has been shown to decrease the pressure of pulmonary artery occlusion in 1 month compared to the control group, but has shown no long-term effects; and the use of mesenchymal precursor cells, which has not been shown to be significantly effective. Final considerations: It is suggested to carry out further studies to improve the indication criteria, making it possible to allocate resources in hospitalized patients.